As-coated thermal barrier coating: structure and chemistry - Chen, Y; Reed, R; Marquis, E (2012)
A thermal barrier coating in the as-processed state is characterized using transmission electron microscopy and atom probe tomography. The structure of the thermally grown oxide correlates strongly with that of the bond coat with alternating regions of mixed alumina/zirconia in contact with γ′ and coarse-grained alumina in contact with γ. Significant Pt and Al diffusion fields are present in γ, but not in γ′. The mechanism by which the structure and chemistry evolves at the TGO/bond coat interface is elucidated. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.